Pd nanowire coatings of laser-treated polyethylene naphthalate: Preparation, characterization and biological response - M. Polivkova; M. Valova; S. Rimpelova; P. Slepicka; V. Svorcik; J. Siegel (eXPRESS Polymer Letters)
Polymeric biomaterials treated by nanostructured metal coatings are very efficient against a wide spectrum of nosocomial pathogens. One of the most effective ways for the preparation of such metal/polymer composites is the combination of excimer laser modification of polymeric materials and vacuum evaporation of noble metals. By this way, we successfully prepared palladium nanowire arrays (PdNWs) supported on biocompatible polyethylene naphthalate (PEN). The characterization of prepared PdNWs on the surface of PEN was accomplished by various methods, such as X-ray Photoelectron Spectroscopy (XPS), Focussed Ion Beam Scanning Electron Microscopy (FIB-SEM), and Atomic Force Microscopy (AFM). PdNWs were preferentially formed from one side of underlying ripples. Pd release in antibacterial testing was measured by Inductively coupled plasma mass spectrometry (ICP-MS). Then, the antibacterial and cytotoxic effects were evaluated by (i) drop plate method using E. coli (G–) and S. epidermidis (G+ bacteria), and (ii) WST-1 cytotoxicity assay with three model cell lines (L929, NIH 3T3, RAW 264.7), respectively. Pd-treated samples exhibited significant antibacterial effects, increasing with cultivation time. Cytotoxicity assay showed that the absorbance of PEN/PdNWs samples was mildly decreased, suggesting considerably low cytotoxic effects of PdNWs.